New product development process through design competencies approach for Malaysia Bumiputera Furniture Manufacturers - Mansor, Nor Hayati (2020)
Despite of strong government support, Bumiputera SME Furniture Manufacturers face some export barriers due to lack of design originality, nil standard NPD process and non-export product quality. Many complex businesses have problems to attract skilled workers also to retain the experienced one. The crisis requires innovative solutions such as accelerated skill application in the whole value chain of product development cycle. This mixed-method study expedites learning process for younger talents and strategy to alleviate knowledge transfer by experienced workers. It contributes to Malaysia Human Capital Development that supports Malaysia Vision 2020. Data was gathered from Bumiputera SME furniture designers with techniques how to mitigate shortage of skilled workers and brain drain issues. The purpose of this research is to study on how can Bumiputera designers’ competencies able to enhance organization capability development which improves product development among Bumiputera SME furniture manufacturers in Malaysia. This study uses literature review to document designers’ competencies, personal traits in Bumiputera SME furniture manufacturing companies during Product Development Cycle. Results of the study includes, recommending key enablers to improve and support process and methods that improve designer’s capabilities. Additionally, the study proposed an operational framework for improving designer competencies where personal competencies development framework and judgment will be enhanced. It included compilation of designer best practices and proposals on how SME furniture manufacturers can accelerate their process in order to move up the value chain. The study thus contributes in enhancing designer capability development. It is expected to accelerate product development, quality and economic benefits in furniture industry in Malaysia.